Eco-friendly ultraviolet spectrophotometric methods for the determination of clotrimazole and tinidazole in bulk and ointment dosage form - Kanaka Parvathi Kannaiah (Growing Science, 2022)
Analyzing a drug over its overlapped spectra utilizes sophisticated instruments and more toxic solvents, which has a deleterious effect on environmental safety. There is an alarming need to develop a simple, novel, and cost-effective method for determining combined substances that are non-toxic to the environment. So, the study aimed to develop four simple, fast and eco-friendly spectrophotometric techniques for quantifying clotrimazole and tinidazole in bulk and ointment dosage form. Stock solutions produced at concentrations of 7 to 13 and 17.5 to 32.5 µg/mL of clotrimazole and tinidazole in 10% v/v ethanol and scanned in the UV-visible range 200-450 nm, and used for all methods. The methods were validated according to the International Council for Harmonization guidelines and found to be within limits. Additionally, the outliers were tested by using the Grubbers test and found within limits. Finally, green evaluation studies show that the method is more environmentally friendly, as confirmed by four assessment tools.